Reciprocal interactions between the human thalamus and periaqueductal gray may be important for pain perception - Wu, D; Wang, S; Stein, J; Aziz, T; Green, A (Springer Nature, 2013)
Pain perception can be altered by activity in the periaqueductal gray (PAG). The PAG can decrease the incoming nociceptive signals at the level of the spinal dorsal horn, but it is not clear whether the PAG can also affect the sensory thalamus, ventral posterolateral and ventral posteromedial thalamic nuclei, to modulate pain. However, the PAG and the thalamus have direct connections with each other; so we postulated that the PAG may also modulate pain by inhibiting the sensory nuclei in the thalamus, and that these may also reciprocally influence the PAG. Here, by analyzing the local field potentials recorded from the sensory thalamus and the PAG in chronic pain patients with deep brain stimulation electrodes, we show that PAG stimulation inhibited the sensory thalamus with decreasing thalamic delta, theta, alpha and beta power, and sensory thalamus stimulation excited the PAG with increasing PAG delta and theta power. We demonstrate that the PAG and the sensory thalamus interact reciprocally at short latency, which may be related to pain modulation.